Peran Permainan Estafet Bola Untuk Meningkatkan Motivasi Belajar Materi Passing Atas dan Bawah Bola Voli Mata Pelajaran PJOK Kelas VII A SMPN 11 Surabaya - Mochamat Rizki Setiawan; Bambang Ferianto Tjahyo Kuntjoro; Ciciek Ismayadewi (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Sports Sport is an activity in human life, both in affective, cognitive and motoric aspects. The ball relay game is a chain ball game that is carried out in groups that trains motor skills and cohesiveness in working together. The purpose of this study was to find out whether the ball relay game could increase the learning motivation of class VII A students at SMPN 11 Surabaya in the subject of passing ata and under volleyball. The type of research used is Classroom Action Research (PTK) or you could say Classroom Action Research. In this study using the Quantitative Descriptive method with systematic data collection techniques using the media in the form of a questionnaire that will be aimed at samples that will be the subject of the study. The results of increasing learning motivation can be seen from the data that has been averaged from questionnaires that have been given to students in various questions that support the influence on learning motivation which in cycle 1 shows an average result of 60.11% and cycle 2 shows an increase motivation to learn up to 82%. From the results of the research it can be concluded that the ball relay game has an effect on increasing the learning motivation of class VII A students of SMPN 11 Surabaya in learning the material of volleyball upper and lower passing which can be seen from the increase from pre-cycle to cycle 2 which always shows improvement.